Building condition assessment supported by Building Information Modelling. (June 2021) - Matos, Raquel; Rodrigues, Fernanda; Rodrigues, Hugo; Costa, Aníbal
Abstract: The buildings natural ageing along with the absence of planned maintenance actions and the effects of climate changes accelerate the building materials degradation. So, to extend the materials' service life, the application of appropriate maintenance actions is imperative. This work aims to assess the building performance and to prioritize the maintenance actions employing Key Performance Indicators using Building Information Modelling-(BIM) as a supporting tool for Building Condition Assessment-(BCA) and maintenance management. To achieve these goals a methodology was proposed and applied to a case study involving 1) Building data collection; 2) Building Life Cycle Cost estimation, and 3) Automated calculation of Building Performance Indicator. This research application highlights the importance of BIM role in buildings' Facility Management, allowing the model's permanent update of information, in this case for BCA purposes. It also has high potential to prioritize the building maintenance actions, extending its materials service life, which contribute to attain a sustainable built environment. Highlights: BIM-based Building Condition Assessment towards a sustainable FM practice. Key Performance Indicators to monitor the buildings' performance. Key Performance Indicators within Building Information Modelling. Maintenance actions prioritizing supported by BIM. Maintenance actions graphic prioritization.